Artikel PROBLEMATIKA PEMBAGIAN WARIS MELALUI SISTEM ACUNGAN DI DESA SINGOROJO PERSPEKTIF KOMPILASI HUKUM ISLAM (KHI) (Studi Kasus Desa Singorojo Kecamatan Mayong Kabupaten Jepara) - Galih Galih Falikhu (At-Ta'aruf : Jurnal Hukum Keluarga Islam, 2023)
This research is the result of field research which aims to find out how the effectiveness of the Compilation of Islamic Law in the distribution of inheritance in a pick-up. And what are the problems that arise when the division of inheritance in acungan. This research uses qualitative methods with the type of field study research and the research approach used is a sociological approach. Primary data sources obtained by researchers are the results of interviews in Singorojo Village and secondary data sources that researchers use are sourced from related books. The data collection techniques were obtained from observation, interviews, documentation and literature. The results of this study indicate that, the division of inheritance in acungan still exists in society. However, the application is rarely realized by the community because it is almost the same as grants or wills. The division of inheritance that occurs in Singorojo village aims to avoid disputes between the heirs. According to the Compilation of Islamic Law, this kind of inheritance division is not recommended because it violates religious rules that require the distribution of inheritance when the heir dies.